Kelompok Kerja Guru Sebagai Determinan Profesionalisme Guru PAUD Formal Di Dinas Pendidikan - Eko Yaketiana; M. Naim Musyafik (Otonomi, 2020)
This study aims to determine the significance of the effect of variable Teacher Working Groups on Teacher Professionalism in the Education Office of Blitar City, to determine the significance of the influence of Motivation on Teacher Professionalism in the Education Office of Blitar City. This research method is quantitative, data collection techniques with questionnaires and documentation. Instrument validity is done by Product Moment analysis, while the reality test uses Cronboch Alfa formula. The results of the study were the Teacher Working Group had a significant effect on the professionalism of formal PAUD Teachers in the Education Office of Blitar City, Motivation had a significant effect on the Professionalism of Formal PAUD Teachers in the Education Office of Blitar City. Education of Blitar City